2010
DOI: 10.1051/0004-6361/200913449
|View full text |Cite
|
Sign up to set email alerts
|

Wide-field multi-color photometry of the Galactic globular cluster NGC 1261

Abstract: Aims. This work studies in more detail the stellar population, including its photometric properties and characteristics, in the rarely studied southern Galactic globular cluster NGC 1261. We focus on the brighter sequences of the cluster's color-magnitude diagram (CMD). Like in our previous works, we rely upon photometry in several passbands to achieve more reliable results and conclusions. Methods. We carried out and analyzed new multi-color photometry of NGC 1261 in UBVI reaching below the turnoff point in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 21 publications
4
27
0
Order By: Relevance
“…We also compare the obtained results with our recent similar findings in NGC 3201 (Kravtsov et al 2010a) and NGC 1261 (Kravtsov et al 2010b). …”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…We also compare the obtained results with our recent similar findings in NGC 3201 (Kravtsov et al 2010a) and NGC 1261 (Kravtsov et al 2010b). …”
Section: Introductionsupporting
confidence: 78%
“…Concerning NGC 3201, in the analysis and plot presented here we used photometric data corrected for differential reddening and decontaminated of field stars as described in Kravtsov et al (2009) and in Kravtsov et al (2010a). All details concerning our photometry in NGC 1261 can be found in Kravtsov et al (2010b).…”
Section: The Observations and Photometric Datamentioning
confidence: 99%
“…While the enriched population has generally been found to be more centrally concentrated than the primordial population within GCs, the majority of the studies to date have not looked at the central regions of clusters, largely due to resolution effects. For example, Carretta et al (2010), Lardo et al (2011), Kravtsov et al (2011), Johnson & Pilachowski (2012, and Beccari et al (2013) have all used ground based observations (photometry and/or spectroscopy) to study the relative spatial distributions of the populations, and have concluded that the enriched population is significantly more centrally concentrated than the primordial one. The above studies have been focused outside the central ∼ 1 for their respective clusters, typically corresponding to 1 − 2 pc.…”
Section: Mixing Of Sub-populationsmentioning
confidence: 99%
“…A similar prediction is made by the early disk accretion model because accretion is more efficient in the central regions where the density is higher. These expectations appear to be borne out by observations of some GCs, where a number of studies have found the enriched stars to be distributed preferentially near the center (Norris & Freeman 1979;Carretta et al 2009b;Kravtsov et al 2010;Lardo et al 2011;Milone et al 2012b). However, the differences in spatial distribution are expected to be eventually erased by dynamical evolution.…”
Section: Introductionmentioning
confidence: 98%
“…So far, they have been detected in NGC 2808 (three main-sequences; D 'Antona et al 2005;Piotto et al 2007), NGC 1851 (double SGB and RGB Milone et al 2008;Han et al 2009), M 4, NGC 3201 and NGC 1261 (two red giant branch populations; Marino et al 2008;Kravtsov et al 2010a,b), as well as in NGC 6752 and 47 Tuc (clear spread of the MS, also RGB spread in NGC 6752; Anderson et al 2009;Milone et al 2010b;Kravtsov et al 2011). In a number of cases (e.g., NGC 1261, NGC 3201, NGC 6752, see Kravtsov et al 2010bKravtsov et al ,a, 2011, evidence exists that the two populations also have different radial distributions, with the redder RGB population being more centrally concentrated. Aside from the aforementioned NGC 1851, Piotto (2008), Marino et al (2009) and Milone et al (2010a) announced preliminary findings of multiple subgiant branches in seven more clusters, among them M 22, M 54, 47 Tuc, NGC 6388.…”
Section: Introductionmentioning
confidence: 96%